The dawn of amphioxus molecular biology: a personal perspective - Holland, P (University of the Basque Country Press, 2017)
The cloning and embryonic expression analysis of an amphioxus Hox gene in 1992 marked the start of molecular analysis of cephalochordate development. Other papers quickly followed, including description of the amphioxus Hox gene cluster in 1994, fuelling a resurgence of interest in a longforgotten animal. I describe the academic background, laboratory experiments and field work leading to the earliest publications in amphioxus molecular developmental biology and explain their scientific impact. The story of amphioxus biology in the 1990s involves collaboration, team work, opportunistic meetings, serendipity, incredulous journal editors, stingrays, airport departure lounges and popcorn.